Training Family Medicine Residents in Effective Communication Skills While Utilizing Promotoras as Standardized Patients in OSCEs: A Health Literacy Curriculum - Pagels, Patti (Int J Family Med, 2015)
Introduction. Future health care providers need to be trained in the knowledge and skills to effectively communicate with their patients with limited health literacy. The purpose of this study is to develop and evaluate a curriculum designed to increase residents' health literacy knowledge, improve communication skills, and work with an interpreter. Materials and Methods. Family Medicine residents (N = 25) participated in a health literacy training which included didactic lectures and an objective structured clinical examination (OSCE). Community promotoras acted as standardized patients and evaluated the residents' ability to measure their patients' health literacy, communicate effectively using the teach-back and Ask Me 3 methods, and appropriately use an interpreter. Pre- and postknowledge, attitudes, and postdidactic feedback were obtained. We compared OSCE scores from the group that received training (didactic group) and previous graduates. Residents reported the skills they used in practice three months later. Results. Family Medicine residents showed an increase in health literacy knowledge (p = 0.001) and scored in the adequately to expertly performed range in the OSCE. Residents reported using the teach-back method (77.8%) and a translator more effectively (77.8%) three months later. Conclusions. Our innovative health literacy OSCE can be replicated for medical learners at all levels of training.